Multi-criteria model for selecting the projects portfolio of companies in business incubators - Gonçalo, Thomas Edson Espíndola (2022)
In a business incubator, the selection of projects to compose the portfolio is an activity of paramount importance for the incubation's success. Given this, the present work aimed to propose a multicriteria model for project selection. Therefore, after defining the objectives, bibliographic research on the theme was carried out. On this basis and after conducting interviews, the multicriteria model was developed, which was applied to an incubator's real case. The model consists of two stages: Pre-incubation and Incubation. In the first stage, a support model for group decision making was proposed to evaluate the alternatives, using the PROMETHEE GDSS method. In the incubation stage, a model to support a multicriteria decision was proposed to select a more efficient portfolio of projects, using the PROMETHEE V method. As a result of the numerical application, it was possible to identify the projects in both stages, maximizing the selection process is earning potential. Thus, considering the lack of studies that analyze this decision making, considering multiple criteria, this article adds to the discussion. For practice, with the application of the model, it is possible to justify decision making, minimizing the potential for conflict in project selection in incubators. For society, there is a more significant potential for a positive return from the performance of business incubators.